2022
DOI: 10.3390/ijms232315010
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Pulsed Stimulation Effectively Improves the Production of Avian Mesenchymal Stem Cell-Derived Extracellular Vesicles That Enhance the Bioactivity of Skin Fibroblasts and Hair Follicle Cells

Abstract: Mesenchymal stem cell (MSC)-derived extracellular vesicles (exosomes) possess regeneration, cell proliferation, wound healing, and anti-senescence capabilities. The functions of exosomes can be modified by preconditioning MSCs through treatment with bio-pulsed reagents (Polygonum multiflorum Thunb extract). However, the beneficial effects of bio-pulsed small extracellular vesicles (sEVs) on the skin or hair remain unknown. This study investigated the in vitro mechanistic basis through which bio-pulsed sEVs enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“… 56 Polygonum multiflorum Thunb extract, which is bio-pulsed reagents, could improve production of chicken embryonic mesenchymal stem cell EVs, and thus enhance the proliferation of human DPCs in vitro, increase expression of follicle activity-related genes IGF-1 and RAC1, cell proliferative genes PNCA and CCND1, and decrease the expression of apoptosis genes TP53 and CASP2 in DPCs. 57 A case report shows that human placenta mesenchymal stem cell EVs could have an effect on permanent chemotherapy-induced alopecia. 58 …”
Section: The Progress Of Exosomes Applied In Hair Growthmentioning
confidence: 99%
“… 56 Polygonum multiflorum Thunb extract, which is bio-pulsed reagents, could improve production of chicken embryonic mesenchymal stem cell EVs, and thus enhance the proliferation of human DPCs in vitro, increase expression of follicle activity-related genes IGF-1 and RAC1, cell proliferative genes PNCA and CCND1, and decrease the expression of apoptosis genes TP53 and CASP2 in DPCs. 57 A case report shows that human placenta mesenchymal stem cell EVs could have an effect on permanent chemotherapy-induced alopecia. 58 …”
Section: The Progress Of Exosomes Applied In Hair Growthmentioning
confidence: 99%
“…Another approach is to pretreat exosome-producing cells to alter exosome properties. Several studies have shown that the pretreatment of MSCs with drugs, cytokines, and physical factors can enhance the effect of MSCs and their exosomes in promoting tissue regeneration [71,[200][201][202][203][204][205][206][207]. The pretreatment method is technically more straightforward, safer, and more universal than genetically engineered exosomes.…”
Section: Engineered Exosomesmentioning
confidence: 99%